Mediating Role of Mindfulness and Self-Regulation in the Relationship between Perceived Stress and Subjective Well-Being Among University Students - Lu Xiong; Rosli Talif; Saeid Motevalli (Iranian Journal of Psychiatry, 2025)
Objective: This study aimed to explore the mediating roles of mindfulness and self-regulation in the correlation between perceived stress and subjective well-being among university students Method: The research involved 353 undergraduates and utilized the Chinese version of the Perceived Stress Scale (CPSS), the Subjective Happiness Scale (SHS), the Mindfulness Attention Awareness Scale (MAAS), and the Self-Regulation Survey (SRS). Partial least square structural equation modelling (PLS-SEM) through SmartPLS software was used to test the proposed relationships. Results: The findings indicated significant relationships among perceived stress, subjective well-being, self-regulation, and mindfulness. Specifically, perceived stress positively predicted mindfulness (β = 0.400, t = 6.233, P < 0.001) and self-regulation (β = 0.441, t = 5.547, P < 0.001). Mindfulness significantly mediated the relationship between perceived stress and subjective well-being (β = 0.241, t = 3.559, P < 0.001), while self-regulation did not exhibit a mediating effect. This suggests that, although self-regulation assists students in managing behaviors and emotions, it may not influence the stress-well-being pathway as effectively as mindfulness does. Conclusion: The results underscore the importance of integrating mindfulness strategies into educational programs to enhance students' mental and emotional well-being. This study provides empirical support for the development of mindfulness-related curricula in universities, suggesting that fostering mindfulness could serve as a pivotal intervention for improving subjective well-being among students facing high levels of perceived stress.